IMPLEMENTASI PASAL 11 AYAT (2) HURUF C PERATURAN GUBERNUR TENTANG NOMOR 60 TAHUN 2016 TENTAN KEDUDUKAN, SUSUNAN ORGANISASI, TUGAS DAN FUNGSI SERTA TATA KERJA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI LAMPUNG (Studi Pada Bagian Perencanaan Sek - Ansori Ansori; Santi Melia (KEADILAN PROGRESIF, 2022)
In implementing regional autonomy, it must ensure that there is a harmonious relationship between the community, the Regional Government must always be oriented towards improving welfare and providing services to the community by taking into account the interests and aspirations of the wider community. The problem in this research is how to implement Article 11 Paragraph (2) Letter C of the Governor's Regulation Number 60 of 2016 concerning the Position, Organizational Structure, Duties and Functions as well as the Work Procedure of the Secretariat of the Regional People's Representative Council (DPRD) of Lampung Province and what are the obstacles to the implementation Article 11 Paragraph (2) Letter C Governor Regulation Regarding Number 60 Year 2016. The research method uses a normative juridical approach and an empirical approach using secondary data and primary data, then qualitative juridical data analysis is carried out. The results of the study, Implementation of Article 11 Paragraph (2) Letter C Governor Regulation Number 60 of 2016 that the DPRD Secretariat has the task of carrying out secretarial administration. So that in carrying out this task, it has the functions of administering the administration of the DPRD and DPRD Financial Administration, holding DPRD meetings, Absorption of aspirations, public relations and DPRD protocols and obstacles to the implementation of Article 11 Paragraph (2) Letter C Governor Regulation Number 60 of 2016 including in budgetary constraints: 1) The nominal budget is always made in excess of the need so as to provide opportunities for interference and corrupt practices, 2) making a budget that can only be understood process for allocating economic resources (budget). Suggestions, the Regional Government should be able to prepare the RPJMD for the next period earlier so thatthe preparation of the RKPD, KUA, PPAS to RKA SKPD can be arranged as effectively as possible in accordance with the budget period to be implemented.